2021
DOI: 10.1002/jgm.3370
|View full text |Cite
|
Sign up to set email alerts
|

E‐cadherin (CDH1) gene –160C/A polymorphism and the risk of colorectal cancer: A meta‐analysis involving 17,291 subjects

Abstract: Background: The E-cadherin (CDH1) polymorphism has been implicated in the susceptibility to colorectal cancer (CRC). However, the results remain inconclusive.The present meta-analysis aimed to investigate the association between the CDH1-160C/A polymorphism and CRC risk.Methods: Relevant studies were retrieved by searching PubMed, Web of Science, Google Scholar, the Cochrane Library, Embase, CNKI and Wanfang databases up to 11 March 2021. Pooled odds ratio and 95% confidence interval were calculated using eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…A critical factor in the virulence of ETBF in CRC is BFT. The expression of BFT induces the cleavage of the extracellular domain of E-calmodulin in the colon epithelium, leading to an increase in epithelial cell permeability and activation of CRC through the β-catenin/Wnt pathway ( Figure 1 ) ( 44 ). Another study found that BFT upregulates spermine oxidase (SMO) in the colonic epithelium, leading to SMO-dependent ROS production and DNA damage ( 45 ).…”
Section: Gut Microbiota and Tumorsmentioning
confidence: 99%
“…A critical factor in the virulence of ETBF in CRC is BFT. The expression of BFT induces the cleavage of the extracellular domain of E-calmodulin in the colon epithelium, leading to an increase in epithelial cell permeability and activation of CRC through the β-catenin/Wnt pathway ( Figure 1 ) ( 44 ). Another study found that BFT upregulates spermine oxidase (SMO) in the colonic epithelium, leading to SMO-dependent ROS production and DNA damage ( 45 ).…”
Section: Gut Microbiota and Tumorsmentioning
confidence: 99%